Molecular mechanisms behind the role of plasmacytoid dendritic cells in systemic sclerosis - Silva, Inês S. (2023)
Systemic sclerosis (SSc) is a debilitating autoimmune disease that affects multiple systems. It is characterized by immunological deregulation, functional and structural abnormalities of small blood vessels, and fibrosis of the skin, and, in some cases, internal organs. Fibrosis has a devastating impact on a patient's life and lung fibrosis is associated with high morbimortality. Several immune populations contribute to the progression of SSc, and plasmacytoid dendritic cells (pDCs) have been identified as crucial mediators of fibrosis. Research on murine models of lung and skin fibrosis has shown that pDCs are essential in the development of fibrosis, and that removing pDCs improves fibrosis. pDCs are a subset of dendritic cells (DCs) that are specialized in anti-viral responses and are also involved in autoimmune diseases, such as SSc, systemic lupus erythematosus (SLE) and psoriasis, mostly due to their capacity to produce type I interferon (IFN). A type I IFN signature and high levels of CXCL4, both derived from pDCs, have been associated with poor prognosis in patients with SSc and are correlated with fibrosis. This review will examine the recent research on the molecular mechanisms through which pDCs impact SSc.